Analisis Kemampuan Pemecahan Masalah Matematika Kelas XI SMAN 55 Jakarta Tahun Ajaran 2022/2023 - Casilta Widianti; Muhammad Giri Tarmizi; Syafira Rizqi Pratiwit (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Problem solving abilities can be used in everyday life to find solutions and solve mathematical problems. The ability to solve mathematical problems in class XI students at SMAN 55 Jakarta for the 2022/2023 academic year is the goal of this research. The research subjects were 36 class XI students consisting of 18 female students and 18 male students at SMAN 55 Jakarta. The research instruments used were interviews, observation, and documentation. The data analysis technique used is qualitative data analysis, namely data reduction, data presentation, drawing conclusions. The research results obtained show the importance of the teacher's role in helping students to solve problems in learning mathematics.